A kinematic analysis of water ski jumping in male and female elite athletes. Issue 8 (17th November 2021) - Nardello, Francesca; Ferrari, Chiara; Spinelli, Luca; Zamparo, Paola
ABSTRACT: The aim of this study was to perform a kinematic analysis of the in-run, take-off and early flight phases in water ski jumping and to analyse the differences in linear/angular parameters between males and females. Forty-two elite skiers participated in this study (27 males; 15 females); their jumps were video recorded during competitions: the time course of absolute (trunk, thigh, ski) and relative (hip, knee, ankle) angles was calculated, as well as the (trochanter) resultant speed. Males were able to reach faster in-run speeds than females (25.4 ± 1.9 and 21.8 ± 1.2 m/s, respectively) and jumped further (56.2 ± 8.6 and 40.4 ± 6.3 m). Longer jumps were correlated with faster speeds in all phases (r range: 0.87–0.91, p < 0.001, n = 42). From take-off to early flight skiers extend their hip (86–109°) and knee (136–171°) angles, lean their trunk forward (49–41°) and raise their skis (20–51°); no major sex differences were observed in the body position (or ski incline) in these phases and none of the angular parameters was correlated with jump distance. Our results suggest that skiers should focus on achieving a larger in-run speed to maximise performance in this discipline.